2015
DOI: 10.1038/ncomms9565
|View full text |Cite
|
Sign up to set email alerts
|

Migration of germline progenitor cells is directed by sphingosine-1-phosphate signalling in a basal chordate

Abstract: The colonial ascidian Botryllus schlosseri continuously regenerates entire bodies in an asexual budding process. The germ line of the newly developing bodies is derived from migrating germ cell precursors, but the signals governing this homing process are unknown. Here we show that germ cell precursors can be prospectively isolated based on expression of aldehyde dehydrogenase and integrin alpha-6, and that these cells express germ cell markers such as vasa, pumilio and piwi, as well as sphingosine-1-phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 33 publications
7
72
0
2
Order By: Relevance
“…In Botryllus schlosseri, we had previously identified a population of germline stem cells (GSCs) that expresses integrin-alpha-6 and vasa [17]. GSCs are found in germline niches in the developing zooids, as well as in the blood.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Botryllus schlosseri, we had previously identified a population of germline stem cells (GSCs) that expresses integrin-alpha-6 and vasa [17]. GSCs are found in germline niches in the developing zooids, as well as in the blood.…”
Section: Resultsmentioning
confidence: 99%
“…In Botryllus schlosseri, germline stem cells are a population of hemoblasts that give rise to gonads during asexual reproduction (palleal budding), whereas all somatic tissues are derived from the parent zooids peribranchial epithelium and not from blood borne cells [14]. In a previous study, we have shown that IA6 is expressed on vasa+ GSC in Botryllus schlosseri [44]. In future studies, we will investigate the similarities and differences between IA6+cells from Botrylloides and from B. schlosseri.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As there are multiple targets downstream FTY720/S1PRs, it is not clear which signal pathway underlies the mechanism. Recently, Kassmer et al reported that the migratory response of germline progenitor cells is dependent on activation of PI3K and Rac1 downstream of the S1P1 [33]. This G-protein-coupled receptors mediate cellular responses to attractive chemokines in a variety of cell types, including NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, this mechanism appears to be conserved, as LPPs also repel germ cells away from nearby somites in the zebrafish 6 . Recently, our group discovered that migration of germ cells is directed by the lysophospholipid Sphingosine-1-phosphate (S1P) in the colonial ascidian Botryllus schlosseri 7 .…”
Section: Introductionmentioning
confidence: 99%